Formation of multiple flagella caused by a mutation of the flagellar rotor protein FliM in Vibrio alginolyticus. (1st August 2022) - Homma, Michio; Takekawa, Norihiro; Fujiwara, Kazushi; Hao, Yuxi; Onoue, Yasuhiro; Kojima, Seiji
Abstract: Marine bacterium Vibrio alginolyticus forms a single flagellum at a cell pole. In Vibrio, two proteins (GTPase FlhF and ATPase FlhG) regulate the number of flagella. We previously isolated the NMB155 mutant that forms multiple flagella despite the absence of mutations in flhF and flhG . Whole‐genome sequencing of NMB155 identified an E9K mutation in FliM that is a component of C‐ring in the flagellar rotor. Mutations in FliM result in defects in flagellar formation ( fla ) and flagellar rotation ( che or mot ); however, there are a few reports indicating that FliM mutations increase the number of flagella. Here, we determined that the E9K mutation confers the multi‐flagellar phenotype and also the che phenotype. The co‐expression of wild‐type FliM and FliM‐E9K indicated that they were competitive in regard to determining the flagellar number. The ATPase activity of FlhG has been correlated with the number of flagella. We observed that the ATPase activity of FlhG was increased by the addition of FliM but not by the addition of FliM‐E9K in vitro. This indicates that FliM interacts with FlhG to increase its ATPase activity, and the E9K mutation may inhibit this interaction. FliM may control the ATPase activity of FlhG to properly regulate the number of the polar flagellum at the cell pole. Abstract : The flagellar rotor generates a driving force to rotate the flagellum and is not involved in controlling the number of flagella in Vibrio. However, we observed that the E9K mutation in the rotor protein FliM confers multiple flagella. Our findings reveal a novel regulatory mechanism controlling flagellar number.